The Implementation of the Reading Aloud Strategy in Enhancing Oral Transactions: Giving and Asking for Information - Sopiah, Siti; Gaffar, Muhammad Andriana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
English is an international language currently used in various ways, including communication. Therefore, English needs to be developed from an early age to improve the ability to interact orally by giving and asking for information according to the basic competence of the subject. This study aims to determine how the Reading Aloud strategy is implemented and what aspects increase when the strategy is applied as a learning method to improve the ability to interact orally in class VIII MTs Darul Falah. This research used a descriptive qualitative approach. The participants used were 33 class VIII students of MTs Darul Falah. Sources of data and information for this research are English teachers and students. Data collection instruments were in the form of observation checklists, field notes, and interviews. Data analysis consists of data reduction, conclusion drawing, and verification. Based on the results of research and discussion, the Reading Aloud method can improve students' ability to interact orally to give and ask for information. The aspects that improved when the Reading Aloud method was implemented in class VIII students of MTs Darul Falah were 1) knowledge aspects consisting of vocabulary, fluency, accuracy and intonation; 2) attitude aspect consisting of respect, caring and self-confidence; 3) behavioral aspects consisting of working together and communicating.